In situ C–H activation-derived polymer@TiO2 p–n heterojunction for photocatalytic hydrogen evolution. Issue 20 (3rd August 2021) - Xing, Yu-Qin; Tan, Zhi-Rong; Cheng, Jing-Zhao; Shen, Zhao-Qi; Zhang, Yu-Jie; Chen, Long; Liu, Shi-Yong
Abstract : Polymer@TiO2 p–n heterojunction photocatalysts are successfully constructed via atom-economic in situ C–H activation polymerization. Abstract : Semiconductor heterojunctions benefiting from efficient charge transfer and separation have been widely used in photocatalysis. Herein, heterojunctions based on polymeric and inorganic semiconductors, namely PyOT@TiO2, have been successfully constructed via in situ C–H activation polycondensation of the pyrene unit (Py-) and 3-(2-(2-ethoxyethoxy)ethoxy)thiophene unit (-OT) in the presence of titanium dioxide (TiO2 ). The combination of the polymeric semiconductor PyOT with TiO2 not only broadens the light response of TiO2, but also dramatically promotes the photo-generation exciton separation of PyOT. As a result, the optimized 50% PyOT@TiO2 composite exhibited extensive visible light absorption (400–520 nm) and the highest photocatalytic hydrogen evolution rate using ascorbic acid (AA) as the sacrificial agent, which is approximately 135 and 21 times higher than those of single-components TiO2 and PyOT, respectively. Mechanistic study by XPS, M–S plots and hydroxyl radical detection tests revealed the p–n heterojunction characteristics of PyOT@TiO2 that contributed to the enhanced photocatalytic performance. Our work develops a promising strategy for the in situ construction of polymeric–inorganic soft–hard heterostructures via atom-economic C–H activation polymerization.